2013
DOI: 10.1248/cpb.c13-00584
|View full text |Cite
|
Sign up to set email alerts
|

Anti-invasion Effect of Crebanine and <i>O</i>-Methylbulbocapnine from <i>Stephania venosa</i> <i>via</i> Down-Regulated Matrix Metalloproteinases and Urokinase Plasminogen Activator

Abstract: The alkaloids isolated from Stephania venosa (S. venosa) have been shown to inhibit the proliferation and to induce the apoptosis of cancer cells. However, the anti-metastatic effect of the alkaloids on cancer cell invasion is unknown. In this study, we investigated the anti-invasive properties of four alkaloids from S. venosa, crebanine (CN), O-methylbulbocapnine (OMBC), tetrahydropalmatine (THP), and N-methyltetrahydropalmatine (NMTHP), in HT1080 human fibrosacroma cells. Treatment of the cells with 15 µg/mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
(40 reference statements)
0
18
0
Order By: Relevance
“…13) Briefly, MDA-MB-231 cells were treated with various concentrations of PRFR (0-20 µg/mL) for 24 h in DMEM serum-free medium. The culture supernatant was collected and separated by 10% polyacrylamide gels containing 0.1% w/v of gelatin in a non-reducing condition.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…13) Briefly, MDA-MB-231 cells were treated with various concentrations of PRFR (0-20 µg/mL) for 24 h in DMEM serum-free medium. The culture supernatant was collected and separated by 10% polyacrylamide gels containing 0.1% w/v of gelatin in a non-reducing condition.…”
Section: Methodsmentioning
confidence: 99%
“…13) Briefly, MDA-MB-231 cells were treated with various concentrations of PRFR for 24 h. The treated cells were washed with ice clod phosphate buffered saline (PBS) and collected by the cell scraper. The cells was lysated with a lysis buffer containing a proteinase inhibitor (50 mM Tris-HCl, 150 mM NaCl, 10 mM, EDTA, 1% Triton X-100, 1 mM phenylmethylsulfonyl fluoride (PMSF), 10 µg/mL leupeptin, 10 µg/ mL aprotinin) for 20 min on ice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, CN has gained much attention due to its biological activities and proven pharmacological safety. 7,8) It was shown that CN more selectively decrease the survival and proliferation of cancerous cell lines than it does normal human fibroblasts.…”
Section: )mentioning
confidence: 99%
“…In recent years, CN has gained much attention due to its biological activities and proven pharmacological safety. 7,8) It was shown that CN more selectively decrease the survival and proliferation of cancerous cell lines than it does normal human fibroblasts.9) Moreover, CN has anti-invasive property in cancer cells by inhibiting constitutive nuclear factor kappa B (NF-κB) activation.10) On the other hand, THP has been stated to possess multi-drug resistant reversing properties in human breast cancer cells.11) These established results have led us to hypothesize that these natural alkaloids may possibly improve the effectiveness of the traditional anticancer drugs.Although the anti-cancer properties of CN have been studied in numerous cancer cell lines, it remains unidentified whether CN has chemo-sensitizing effect on drug-resistant cancer cells. Therefore, the purpose of the present study was to determine whether CN and its natural analogues show chemo-sensitizing effects in response to platinum drug in human…”
mentioning
confidence: 99%